منهج ابن حجر العسقلاني في تعليل الأحاديث بالاختلاف من خلال كتاب الإصابة في تمييز الصحابة: Ibn Ḥajar’s Methodology in Identifying Hadith Defects Through Narratorial Variations in Al-Iṣābah - Maulana Maulana (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study examines al-Ḥāfiẓ Ibn Ḥajar’s methodology in presenting and evaluating hadiths deemed defective due to discrepancies in transmission (ikhtilāf al-riwāyah) in al-Iṣābah fī Tamyīz al-Ṣaḥābah, analyzing his critical judgments in light of established principles of hadith criticism. Although al-Iṣābah is primarily a biographical dictionary of the Companions and those mistakenly regarded as such, it contains more than one thousand hadiths identified by Ibn Ḥajar as defective. In this respect, the work deserves recognition as an important source in the science of ʿIlal al-Ḥadīth, although this aspect has received little scholarly attention. This study explores Ibn Ḥajar’s methodology in presenting hadiths affected by narratorial discrepancies, identifying their hidden defects, and preferring one narration over another. It also assesses his mastery of the science of ʿilal and the extent to which his methodology corresponds to that of the leading early hadith critics. The research employs a descriptive-analytical approach supported by an inductive examination of relevant hadith materials in al-Iṣābah. Selected narrations are analyzed according to established principles of hadith criticism, with attention to Ibn Ḥajar’s critical observations and judgments. The findings show that Ibn Ḥajar was a leading authority in the science of ʿilal and hadith criticism, that al-Iṣābah should be regarded as an important source for the study of hidden defects in hadith, and that his methodology closely resembles that of early critics such as Aḥmad ibn Ḥanbal, Abū Ḥātim, and al-Dāraquṭnī.